Opioid Prescribing for Chronic Musculoskeletal Conditions: Trends over Time and Implementation of Safe Opioid-Prescribing Practices - Wally, Meghan K.; Thompson, Michael E.; Odum, Susan; Kazemi, Donna M.; Hsu, Joseph R.; Seymour, Rachel B.; and PRIMUM Group (Applied Clinical Informatics, 2023)
Objectives This study aimed (1) to determine the impact of a clinical decision support (CDS) tool on rate of opioid prescribing and opioid dose for patients with chronic musculoskeletal conditions and (2) to identify prescriber and facility characteristics associated with adherence to the Centers for Disease Control and Prevention guideline for prescribing opioids for chronic pain in this population.We conducted an interrupted time series analysis to assess trends in percentage of patients from 2016 to 2020, receiving an opioid and the average opioid dose, as well as the change associated with implementation of the CDS toolkit. We conducted a retrospective cohort study to assess the association between prescriber and facility characteristics and safe opioid-prescribing practices.Methods We assessed the impact of the CDS intervention on percent of patients receiving an opioid and average opioid dose (morphine milligram equivalents). We operationalized safe opioid prescribing as a composite score of several behaviors (i.e., prescribing naloxone, initiating a pain agreement, prescribing <90 MME, avoiding extended-release prescriptions for opioid-naïve patients, and avoiding coprescribing opioids and benzodiazepines) and used a hierarchical linear regression model to assess associations between prescriber and facility characteristics and safe opioid prescribing.Results This CDS intervention had a modest but statistically significant 1.6% reduction on the percent of patients (n = 1,290,746) receiving an opioid (mean: 15% preintervention; 10% postintervention). The average dose of opioid prescriptions did not significantly change. Advanced practice providers and prescribers with higher percentages of patients aged 18 to 64 exhibited safer opioid prescribing, while prescribers with higher percentages of white patients and larger numbers of patients on opioids exhibited less safe opioid prescribing.Conclusion A CDS intervention was associated with a small improvement in percent of patients receiving an opioid, but not on average dose. Clinicians are not prescribing opioids for chronic musculoskeletal conditions frequently, when they do, they are generally adhering to guidelines.
Keywords: opioids; musculoskeletal pain; chronic pain; clinical decision support; implementation; alert